Urothelial carcinoma arising from an ovarian mature cystic teratoma - Hui-Yu Chuang; Yi-Ting Chen; Tak-Loi Mac; Yu-Chieh Chen; Hung-Sheng Chen; Wan-Shan Wang; Eing-Mei Tsai (Taiwanese Journal of Obstetrics & Gynecology, 2015)
Objective: Ovarian mature cystic teratomas with malignant transformation are rare, and squamous cell carcinoma is the most common pathological entity. Among these malignant transformations, urothelial cell carcinoma is rare. Case Report: We report a woman presenting with a huge pelvic cystic mass, favoring a right ovarian mature cystic teratoma with malignant transformation, based on magnetic resonance imaging, who was successfully treated with surgery. Conclusion: The final pathology confirmed concomitant malignant transformation of urothelial carcinoma.